Pembelajaran Pendidikan Agama Islam Selama Pandemi Covid-19 di Indonesia - Hafizh Idri Purbajati (FALASIFA : Jurnal Studi Keislaman, 2021)
The Covid-19 pandemic that has hit the whole world has had a very significant impact on human life in various fields. Education is one of the areas affected. This requires educational institutions to be able to adapt to the real conditions that are happening. Islamic Religious Education during the Covid-19 pandemic can be carried out using various existing media. Information and communication technology is one of the factors supporting the implementation of these activities. Learning Islamic Religious Education online even provides a number of positive benefits. This can also be one of the factors to realize an advanced and world-class Islamic Education. This article tries to discuss the implementation of online Islamic Religious Education learning, the challenges, and alternatives that can be taken to realize effective learning activities during the Covid-19 pandemic.